2016
DOI: 10.1371/journal.pone.0144497
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immortal Cell Lines Support Cellular Heterogeneity in the Human Annulus Fibrosus

Abstract: IntroductionLoss of annulus fibrosus (AF) integrity predisposes to disc herniation and is associated with IVD degeneration. Successful implementation of biomedical intervention therapy requires in-depth knowledge of IVD cell biology. We recently generated unique clonal human nucleus pulposus (NP) cell lines. Recurring functional cellular phenotypes from independent donors provided pivotal evidence for cell heterogeneity in the mature human NP. In this study we aimed to generate and characterize immortal cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 57 publications
4
39
0
Order By: Relevance
“…In support of our data, it was recently shown by RNA in situ hybridization that NP and transition zone cells, which did not have a NC morphology, express bKrt19 [26]. Moreover, we previously found that Brachyury/T mRNA and protein levels do not necessarily match in mature human NP cells [10]. A detailed age range should be performed on the histological level to determine the rate of NC depletion in the bovine tail IVD.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In support of our data, it was recently shown by RNA in situ hybridization that NP and transition zone cells, which did not have a NC morphology, express bKrt19 [26]. Moreover, we previously found that Brachyury/T mRNA and protein levels do not necessarily match in mature human NP cells [10]. A detailed age range should be performed on the histological level to determine the rate of NC depletion in the bovine tail IVD.…”
Section: Discussionsupporting
confidence: 88%
“…Previously we used six NP specific marker genes to discriminate cultured human NP from AF cells [10]. We hypothesized that these genes would be able to distinguish the NP from inner AF tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The glycosaminoglycan keratan sulfate was identified in the inner and outer AF of the developing rat IVD, and has also been identified in human AF tissue as a specific matrix protein of annulocytes . A transcriptional signature of COL1A1, COL5A1, COL12A1 , and SFRP2 was proposed for a population of annulocytes isolated from young human tissue after culture . The association of type XII collagen with type I collagen is well established and is thought to modify the interactions between collagen I fibrils and surrounding matrix.…”
Section: Cells Of the Annulus Fibrosusmentioning
confidence: 99%
“…The association of type XII collagen with type I collagen is well established and is thought to modify the interactions between collagen I fibrils and surrounding matrix. SFRP2 , a modulator of Wnt signaling, is a putative AF marker specific to outer annulocytes in human and bovine tissue . Outer annulocytes share similar markers to other dense, fibrous connective tissue cells, such as tenocytes and ligamentocytes, including the genes Tnmd, Mkx , and Scx in human, bovine, and murine AF …”
Section: Cells Of the Annulus Fibrosusmentioning
confidence: 99%